Improvement of a microfilter prototype and its realization: chemical applications - Baydyk, Tetyana; Mammadova, Masuma; Herrera, Graciela Velasco; Kussul, Ernst (Private Company Technology Center, 2025)
The object of this research is microfilters. This study aims to develop a microfilter that can be used, for example, for air or water f iltration as traditional applications. The closed indoor environments demand the control of the air quality for the health of humans who work there. The implementation of different technologies as MicroElectroMechanical Systems (MEMS), NanoElectroMechanical Systems (NEMS) and MicroEquipment Technology (MET) for microcomponents production is analyzed. The advantages and disad vantages of these technologies are described. MET was used to produce and develop microfilter structure. The structffure and model of the microfilter is presented. The problem to be solved is connected with microfilter structure simplification and preparation it for the use of new technologies for their production. For its realization the 3D printer was used. 3D printers are the equipment that realizes an additive technology that has been actively developed in recent years. From computer 3D model it is possible to build the 3D prototype. The essence of the results is the possibility of mass production of microfilters. Different possible applications, not only filtration of air and liquid are described, but applications in chemistry for microreactions module and microseparation units. It was compared new microfilter design with our previous prototype of microfilter developed and produced using the MET. The MET has advantage that it works with various materials and not just those used in microelectronics. Their tests and investigations demonstrated that the microfilters can be used in practice. New prototype was made by 3D printer. Comparative assessment of the first microfilter prototype and new prototype shows that the new prototype has a simplified structure and is easier to manufacture. One of the most interesting areas of their applications is for chemical microreactors. It is one of the new, interesting and promising areas of application